Statistical Analysis And Optimization Of A Low Noise Amplifier Operating At 5.8 Ghz ISM Band - Ahmad, Nur Ainina (UTeM, 2009)
This thesis presents the work done on the design of a low noise amplifier. The purpose of the amplifier is to amplify the received RF path of a Wireless Local Area Network (WLAN). The transistor FHX76LP was chosen over others due to the simplest configuration it offers for an amplifier design. Several measurement techniques are by using Microwave Office and Advanced Design System 2005A (ADS). Calculations are by using MathCad. The amplifier performed reasonably well for the required frequency band which is 5.8 GHz on the tests of power gain which achieved 38.482 dB and noise figure of 0.891 dB, thereby closely matching the measured readings with the simulated results.